MEDIA SOSIAL SEBAGAI SARANA KOMUNIKASI KANDIDAT PADA PEMILIHAN KEPALA DAERAH DI KOTA MAKASSAR TAHUN 2020 - Saputro, Eko Rachmat (Jurnal Politik Profetik, 2022)
This study aims to explain the use of social media by candidates for Mayor in the Election of Mayor and Deputy Mayor of Makassar in 2020. This study uses a qualitative content analysis method. The results of the study show that the campaign efforts carried out by candidates for Mayor and Deputy Mayor of Makassar are through social media with content related to candidate pairs, program delivery, and visits using the help of influencers. In addition, content delivery is also carried out using hashtags on Instagram and using podcasts that are shared on the Instagram accounts of each candidate pair. This effort is quite influential in influencing the choices of millennials in Makassar City because the content presented is packaged innovatively so that the delivery of political messages can influence novice voters in Makassar City.